Shadows of rediscovered tradition: Postconciliar perspective on relations between the bishops of Rome and Spain in the First millennium : A review of: Ferreiro, A. (2020). Epistolae Plenae: The Correspondence of the Bishops of Hispania with the Bishops of Rome (Third through Seventh Centuries). Brill. 336 p. - S. A. Vorontsov (Шаги)
Нет аннотации